Aspek Sosial Ekonomi Penambang Pasir di Desa Tomoahi Kecamatan Kulisusu Kabupaten Buton Utara - Azmul, Azmul; Bafadal, Azhar (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
This study aimed to analyze the social and economic aspects of the sand miners in the village Tomoahi District Kulisusu North Buton. Sampling was done by census. Methods of data analysis using the formula I = revenue TR-TC, and descriptive analysis. Population acquired 46 people as respondents. The collection of data by conducting research in the field and interviews. The results showed that the sand mining activities in the village Tomoahi a positive effect on social and economic aspects of society, which can increase people's income, employment creation and increase business opportunities. Besides, the sand mining has negative effect , but can betolerated because of its positive impact is quit e large